Perlindungan Hukum Terhadap Pihak Yang Dirugikan Akibat Pemalsuan Akta Otentik Oleh Notaris (Studi Kasus Putusan Nomor: 466/Pid.B/2023/PN Jkt.Sel) - Seruni, Puspa (VIVA THEMIS, 2025)
This research analyses legal protection for parties who suffer losses due to falsification of authentic deeds carried out by notaries in Decision Number: 466/Pid.B/2023/PN JKT.Sel and legal protection for notary positions and what is the impact on the parties of falsified authentic deeds by a notary in Decision Number: 466/Pid.B/2023/PN JKT.Sel. The research method used is a normative legal research method using a statutory approach and a case approach. The results of this research indicate that legal protection for parties who are victims of forgery of authentic deeds carried out by notaries in the case of Decision Number: 466/Pid.B/2023/PN/Jkt.Sel is repressive legal protection in the form of settlement, namely in the form of material compensation amounting to Rp. 150,000,000,000,- and immaterial compensation in the form of loss of the victim's reputation both in the family, community and work environment, while legal protection for the position of notary is contained in Article 66 UUJN. The impact for the parties of the falsification of an authentic deed carried out by a notary in the case of Decision Number: 466/Pid.B/2023/PN/Jkt.Sel is that there is material and immaterial loss due to the notary making a deed containing false information and the cancellation of the deed authentic actions carried out by the court because they contain unlawful acts